THE EFFECT OF TRAINING OF TEACHERS ON THE IMPLEMENTATION OF HIV AND AIDS EDUCATION IN SECONDARY SCHOOLS IN HAMISI SUB-COUNTY IN KENYA - Esiokhunjila Nganyi, Dr. Jason; Likunda Nganyi, David; Anangwe, Josephine (IJRDO - Journal of Social Science and Humanities Research, 2016)
So far, HIV and AIDS has no cure and no vaccine, but education has been termed as a ‘social vaccine’ due to the important role it can play in the fight against HIV and AIDS. This is so because education empowers individuals with appropriate skills and knowledge that can fight HIV and AIDS. According to United Nations joint programme on HIV and AIDS (UNAIDS) released in July, 2008, Kenya had been dropped from the list of most successful countries in Africa in controlling the spread ofHIV and AIDS. The purpose of the study was to establish the effect of training on implementation of HIV and AIDS education in secondary schools. Descriptive survey research design was used in this study. The sample of 19 teachers and 122 teachers was selected through stratified and purposive sampling techniques. Data was collected by use of questionnaires. Data from questionnaire was analyzed using descriptive statistics where frequencies and percentages were used. The findings revealed that most teachers had undergone HIV and AIDS training. The study recommends that the Ministry of Education and the Teachers Service Commission should facilitate more training of teachers on the management and control ofHIV and AIDS, hence improve the provision ofHIV and AIDS education.